Comparative Analysis of the Microstructure and Tribological Behaviors of Ni-, Fe-, and Co-Based Plasma Cladding Coatings - Tiantian He; Jie Tian; Zeyuan Liu; Gaoang Song; Sanming Du; Yongzhen Zhang (Metals)
Nickel-, iron-, and cobalt-based alloy coatings were fabricated on the surface of U75V steel utilizing plasma cladding technology. This study investigates the microstructure, mechanical properties, and tribological performance of the coatings. The findings reveal that the microstructure of the coatings predominantly consists of dendritic and eutectic structures. The surface microstructure exhibited a dense, continuous, and uniform morphology. Following the cladding process, the samples were characterized by residual compressive stress. In comparison to the substrate, the hardness of the Ni-, Fe-, and Co-based coatings increased by 141%, 101%, and 44%, respectively; the wear rates of these coatings decreased by 36.6%, 22.1%, and 11.7%, respectively. The wear mechanisms of the Ni- and Fe-based coatings were predominantly adhesive wear; however, the extent of adhesive wear of the Fe-based coating was more obvious than that of the Ni-based coating. By contrast, the Co-based coating exhibited abrasive wear, which was the most severe among the three types of coatings. Additionally, the Ni-based coating demonstrated the lowest friction coefficient and wear rate, thereby exhibiting superior wear resistance compared to the other two coatings.